Clinical characteristics of Kawasaki disease with pulmonary radiographic abnormalities and its impact on the incidence of coronary artery lesions: a randomized retrospective cohort study - Liu, Chenchen; Rong, Xing; Qiu, Huixian; Zhou, Jinhui; Chen, Yufei; Huang, Xuhong; Chu, Maoping; Wang, Zhenquan (Frontiers in Pediatrics, 2025)
ObjectiveThe aim of this study was to investigate the characteristics of Kawasaki disease (KD) in patients demonstrating pneumonia-like changes and pulmonary complications, as well as the subsequent impact on coronary artery lesions, by comparing them with those of KD patients with normal pulmonary imaging.MethodFrom January 1, 2013 to October 1, 2022, this study included paediatric patients diagnosed with KD who were registered in the KD database at Yuying Children's Hospital affiliated with Wenzhou Medical University. Patients were divided into three distinct groups based on the presence and severity of abnormalities observed via lung imaging. We first compared the demographic and clinical characteristics across these groups. The imaging characteristics of KD patients with pneumonia-like changes and pulmonary complications were identified via chest radiography (x-ray) and chest computerized tomography (CT). Logistic regression models and stratified analyses were employed to further identify factors influencing coronary artery lesions (CALs).ResultsAmong the 2,686 KD children admitted to our centre in recent years, 115 presented with pneumonia-like changes, 366 presented with pulmonary complications, and 495 presented with no evident abnormalities on chest radiographs. In KD patients with pneumonia-like changes, there were significant elevations in inflammatory markers including the C-reactive protein (CRP) (P = 0.011), white blood cell (WBC) (P = 0.027), NT-proBNP (P = 0.007), and D-dimer (D-D) (P = 0.002) levels. Imaging studies have frequently revealed bilateral lung infections, predominantly in the mid-lower lung fields. Bronchitis-related changes were the most common manifestation of pulmonary complications in KD patients. A significant difference was observed in the incidence of CALs among patients with pneumonia-like changes. After adjusting for confounding variables, patients with pneumonia-like changes had a greater likelihood of developing CALs, with an adjusted odds ratio (OR) of 1.94 [95% confidence interval (CI): 1.21, 3.11]. Similar findings were obtained through stratification and sensitivity analyses.ConclusionPatients diagnosed with KD who develop pneumonia-like changes and related pulmonary complications can be identified based on their clinical manifestations and imaging characteristics. Moreover, patients with KD and pneumonia-like changes had a significantly increased risk of developing CALs.